Microglia-derived exosomal circZNRF1 alleviates paraquat-induced neuronal cell damage via miR-17-5p - Xu Liu; Qingqing Wu; Jingwen Wu; Jianxi Liu; Fuli Zheng; Guangxia Yu; Hong Hu; Zhenkun Guo; Siying Wu; Huangyuan Li; Wenya Shao (Ecotoxicology and Environmental Safety, 2023)
Paraquat (PQ) is an environmental poison that causes clinical symptoms similar to those of Parkinson's disease (PD) in vitro and in rodents. It can lead to the activation of microglia and apoptosis of dopaminergic neurons. However, the exact role and mechanism of microglial activation in PQ-induced neuronal degeneration remain unknown. Here, we isolated the microglia-derived exosomes exposed with 0 and 40 μM PQ, which were subsequently co-incubated with PQ-exposed neuronal cells to simulate intercellular communication. First, we found that exosomes released from microglia caused a change in neuronal cell vitality and reversed PQ-induced neuronal apoptosis. RNA sequencing data showed that these activated microglia-derived exosomes carried large amounts of circZNRF1. Moreover, a bioinformatics method was used to study the underlying mechanism of circZNRF1 in regulating PD, and miR-17–5p was predicted to be its target. Second, an increased Bcl2/Bax ratio could play an anti-apoptotic role. Bcl2 was predicted to be a downstream target of miR-17–5p. Our results showed that circZNRF1 plays an anti-apoptotic role by absorbing miR-17–5p and regulating the binding of Bcl2 after exosomes are internalized by dopaminergic neurons. In conclusion, we demonstrated a new intercellular communication mechanism between microglia and neurons, in which circZNRF1 plays a key role in protecting against PQ-induced neuronal apoptosis through miR-17–5p to regulate the biological process of PD. These findings may offer a novel approach to preventing and treating PD.